The tongues of angels - Price, Reynolds 1933-2011 (Atheneum, 1990)
Two themes seem central to all Reynolds Price's work--the twin powers of memory and of artistry. In this new novel, a middle-aged painter recalls the events and people of the year he turned twenty-one--in particular a gifted young boy, "whose death I may have caused". His reminiscences of that long-ago time reveal the crucial forces that shaped him as an artist and as a man.
Keywords: Artists -- Fiction; Friendship in children -- Fiction; Psychological fiction